Implementasi Chatbot Berbasis Dialogflow dengan Metode Natural Language Processing untuk Rekomendasi Tempat Wisata di Kabupaten Kulonprogo - Khotama, Faizal Wahyu; Yulianton, Heribertus (STIKOM Tunas Bangsa Pematangsiantar, 2025)
This research is based on the importance of providing quick and accurate tourism information in Kulonprogo Regency. The problem addressed in this study revolves around how to implement a Dialogflow-based chatbot utilizing Natural Language Processing (NLP) technology to effectively recommend tourist destinations. The objective of this research is to design and test a chatbot capable of understanding users' natural language and providing relevant tourism recommendations. The research methodology includes data collection through interviews, observations, and document studies, as well as system design based on conversational flows and intents. Testing results indicate that the chatbot achieved 100% accuracy in black-box testing and an average score of 85 on the System Usability Scale (SUS) evaluation, demonstrating high user satisfaction. In conclusion, this chatbot provides an interactive and responsive solution to promote local tourism and improve the accessibility of tourism information for users.